Representasi Etnis Tionghoa dalam Film “Ku Kejar Cinta Ke Negeri Cina” dan “Ngenest” - Rina Sari Kusuma; Zamratush Sholihah (MediaTor (Jurnal Komunikasi), 2018)
The construction of representations of certain groups in the mass media reflects existing power relations. This is what happened to the description of Chinese in Indonesian films. Ethnic representation reflects the social, cultural, political, and economic values of the people who produce it. Government policies related to the existence of ethnic Chinese in Indonesia have been issued several times. Through Presidential Decree No. 12 in 2014 the government again made a regulation that tried to place Chinese people not to be seen and treated discriminatively. The purpose of this study was to determine the description of ethnic Chinese characters in films in Indonesia after the issuance of the regulation. By using semiotic analysis, researchers wanted to see the depiction in the film Ku Kejar Cinta ke Negeri Cina and Ngenest. The results show that the image of Chinese ethnicity is still maintained, which is related to physical problems, religion, and national identity, while the changing depiction relates to social class that are economy and education. The retention of these Chinese portrayals shows that government interference through regulation has not been able to change the general view of Chinese ethnicity.